The use of bimetallic heterogeneous oxide catalysts for the Fenton reaction - Mgedle, Nande (Vaal University of Technology, 2019)
Water contaminated with non-biodegradable organics is becoming increasing problematic as it has a hazardous effect on human health and the aquatic environment. Therefore, the removal of organic contaminants is of importance and an active heterogeneous Fenton catalyst is thus required. The literature indicates that a bimetallic oxide Fenton catalyst is more active than an iron oxide catalyst. This study focused on increasing the activity of iron-based Fenton catalysts with the addition of transition metals such as manganese, cobalt and copper and optimizing the preparation method. In this study, bimetallic oxide (Fe-Cu, Fe-Mn, Fe-Co) and monometallic oxide (Fe, Cu, Mn,Co) catalysts supported on silica SiO2 where prepared by incipient wetness impregnation. The total metal oxide contents were kept constant. The catalysts where calcined in two different ways, in a conventional oven and in a microwave. These catalysts were characterized with XRD, XPS and CV and were tested for the degradation of methylene blue dye at 27°C. The catalysts calcined in a microwave oven had a higher catalytic activity than those prepared in a conventional oven. The bimetallic oxide catalysts outperformed the mono- metallic oxide catalysts in the degradation of methylene blue. The Fe2MnOx prepared by microwave energy were the most active catalyst yielding the highest percentage of degradation of methylene blue dye (89.6%) after 60 minutes. The relative amounts of manganese and iron oxide were varied while keeping the total metal content in the catalyst the same. The optimum ratio of Fe to Mn was 1:7.5 since it yielded the most active catalyst. A 96.6 % removal of methylene blue was achieved after 1 hour of degradation. Lastly this ratio 1Fe:7.5Mn was prepared by varying different microwave power (600, 700 and 800 W) and irradiation time (10, 20 and 30 min). The optimum microwave power and irradiation time was 800W and 10 min with the methylene blue percentage removal of 96.6 % after 1 hour of degradation.
M.Tech. (Department of Chemistry, Faculty of Applied and Computer Sciences), Vaal University of Technology
Keywords: Water contamination; Non-biodegradable organics; Monometallic oxide; Bimetallic oxide Fenton catalyst; Iron oxide catalyst; Dissertations, Academic -- South Africa; Environmental chemistry; Iron oxides; Water -- Pollution